Tucker & Dale vs. evil [videorecording (DVD)] - Craig, Eli, 1972-; Tudyk, Alan; Moss, Jesse, 1983-; Bowden, Katrina, 1988-; Labine, Tyler, 1978- (Magnet Releasing : [Distributed by] Magnolia Home Entertainment, 2011)
Two friends on vacation at their dilapidated mountain house are mistaken for murderous backwoods hillbillies by a group of obnoxious, preppy college kids. When one of the students is separated from the group, the boys try to lend a hand, but as the misunderstanding grows, so does the body count and the laughs.